Bioreactor-engineered cancer tissue-like structures mimic phenotypes, gene expression profiles and drug resistance patterns observed "in vivo". (September 2015) - Hirt, Christian; Papadimitropoulos, Adam; Muraro, Manuele G.; Mele, Valentina; Panopoulos, Evangelos; Cremonesi, Eleonora; Ivanek, Robert; Schultz-Thater, Elke; Droeser, Raoul A.; Mengus, Chantal; Heberer, Michael; Oertli, Daniel; et al.
Abstract: Anticancer compound screening on 2D cell cultures poorly predicts "in vivo" performance, while conventional 3D culture systems are usually characterized by limited cell proliferation, failing to produce tissue-like-structures (TLS) suitable for drug testing. We addressed engineering of TLS by culturing cancer cells in porous scaffolds under perfusion flow. Colorectal cancer (CRC) HT-29 cells were cultured in 2D, on collagen sponges in static conditions or in perfused bioreactors, or injected subcutaneously in immunodeficient mice. Perfused 3D (p3D) cultures resulted in significantly higher (p < 0.0001) cell proliferation than static 3D (s3D) cultures and yielded more homogeneous TLS, with morphology and phenotypes similar to xenografts. Transcriptome analysis revealed a high correlation between xenografts and p3D cultures, particularly for gene clusters regulating apoptotic processes and response to hypoxia. Treatment with 5-Fluorouracil (5-FU), a frequently used but often clinically ineffective chemotherapy drug, induced apoptosis, down-regulation of anti-apoptotic genes ( BCL-2, TRAF1, and c-FLIP ) and decreased cell numbers in 2D, but only "nucleolar stress" in p3D and xenografts. Conversely, BCL-2 inhibitor ABT-199 induced cytotoxic effects in p3D but not in 2D cultures. Our findings advocate the importance of perfusion flow in 3D cultures of tumor cells to efficiently mimic functional features observed "in vivo" and to test anticancer compounds.